UK Foreign Policy and Intelligence in the Post-Truth Era: Radical Violent Extremism and "Blow-Back". (1st October 2017) - ,
Abstract : Recent terrorist attacks in the UK have raised questions over the relationship between Britain's foreign policy and terrorist attacks in the UK. The main arguments made by Labour Party leader Jeremy Corbyn, his critics and the views of those charged with defending the UK from terrorism are summarized. The article argues that the UK government's reasons for denying a relationship between foreign policy and terrorist attacks are because of (1) evidence that Britain's foreign policies have contributed to violent radical extremism and (2) links between some "terrorists", designated jihadist groups and Britain's intelligence services.